PRINCIPAIS FALHAS NO PLANEJAMENTO DE MÉDIO PRAZO DE OBRAS: UMA REVISÃO SISTEMÁTICA DA LITERATURA - Angelim, Vanessa Lira; Alves, Thais da Costa Lago; Lima, Mariana M. Xavier de; Barros Neto, José de Paula (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Construction production systems have intrinsic characteristics that make them complex systems that require the use of efficient processes to assure project performance goals are met. Planning and control systems like the Last Planner System of Production Control (LPS ), which define different planning levels, are employed to address these issues. The mediumterm level (MTL), which is essential to assure plans are executed as planned at the master (milestone) schedule level, is one of these levels. This paper uses a theoretical-conceptual approach based on a structured literature review aiming at identifying the main shortcomings related to MTL use in construction projects. Results indicate inefficiencies in the way it is used, and the most common ones include improperly developing/implementing MTL plans, failure to connect the MPL with different planning levels, failure to identify and remove constraints, and lack of indicators to evaluate the MPL performance. In summary, additional research is needed to support the efficient use of MTL in construction projects, especially considering that the MPL plays an important role to remove constraints that impact activities and promote continuous flow, which are essential to achieving project goals related to time, cost, quality, and safety.